Design and Construction of Electronic Vote System in State Polytechnic of Jakarta - Saptio, Janwari Farqi; Waluyo, Yoyok Sabar (POLITEKNIK NEGERI JAKARTA, 2015)
Background of many problemis abuse of ballots up to cost in the implementation of election in Indonesia. The vast area of Indonesia was be a reason difficulty of monitoring functions, the amount of funds on each election. Another problem is the lack of voter participant onon election., even though, government have expend a lot funds for that election. The reason of less participant is be caused the length of time to wait or line up in do services and long TPStook place. That matter is a reason why researche tries to build and develop some election application which can be easy to access by all Indonesian public with good secure data as well. This application is easy to use with a single ID for vote like e-KTP, KTM and others. Use this single ID has a purpose to avoid redundancies of data, because Single ID is only for one of characteristic of the owner. The method to build this application uses the Waterfall Model and Extreme Programming model by conducting analysis phase, design phase, implementation phase, testing phase, and evaluation phase. Conclusion of this problem is that by using e-vote or e-election can make easy and up the accelerate of data processs. This article describe to implement the system by making a prototype in the case of PEMIRA in State Polytechnic of Jakarta.